2000
DOI: 10.1002/(sici)1097-4628(20000328)75:13<1569::aid-app2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in mechanical properties of poly(p-phenylene sulfide) fibers by high-tension multiannealing method

Abstract: High‐tension multiannealing (HTMA) was applied to improve the tensile properties of poly(p‐phenylene sulfide) fibers, which was furthermore applied to the fibers produced and improved with the zone‐drawing and zone‐annealing treatments. The HTMA treatment was repeatedly applied to the fibers under the conditions of a 250°C temperature and an applied tension of between 201.0 and 188.0 MPa. As a result, at the 13th treatment the degree of crystallinity increased to 40%. On the other hand, the orientation factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…It is known that the mechanical properties of the polymers can be signicantly enhanced through the stretching processes. [13][14][15][16][17] For PLA, Maspoch et al 18 and Wu et al 19 previously reported that the mechanical properties of drawn PLA lms, including the modulus, tensile strength, and elongation at break, were simultaneously improved compared with the undrawn lms. More recently, Jariyasakoolroj et al 20 claried that the isotropically small crystalline lamellae formed in the biaxial stretching process was the key microstructure to obtain PLA with excellent performance (180 MPa tensile strength and 80% elongation at break).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the mechanical properties of the polymers can be signicantly enhanced through the stretching processes. [13][14][15][16][17] For PLA, Maspoch et al 18 and Wu et al 19 previously reported that the mechanical properties of drawn PLA lms, including the modulus, tensile strength, and elongation at break, were simultaneously improved compared with the undrawn lms. More recently, Jariyasakoolroj et al 20 claried that the isotropically small crystalline lamellae formed in the biaxial stretching process was the key microstructure to obtain PLA with excellent performance (180 MPa tensile strength and 80% elongation at break).…”
Section: Introductionmentioning
confidence: 99%